2013
DOI: 10.1016/j.jfoodeng.2013.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of whey protein isolate films reinforced with porous silica coated titania nanoparticles

Abstract: Whey protein isolate (WPI) films embedded with TiO2@@SiO2 (porous silica (SiO2) coated titania (TiO2)) nanoparticles for improved mechanical properties were prepared by solution casting. A WPI solution of 1.5 wt% TiO2@@SiO2 nanoparticles was subjected to sonication at amplitudes of 0, 16, 80 and 160 μm prior to casting in order to improve the film forming properties of protein and to obtain a uniform distribution of nanoparticles in the WPI films. The physical and mechanical properties of the films were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…Zhou et al (2009) used 4% TiO 2 and observed a 70% decrease in WVP while Zolfi et al (2014) and Li et al (2011) observed 14% and 9.4% decreases by adding 5% and 1% TiO 2 , respectively. Kadam et al (2013) and Sothornvit et al (2009) did not obtain any gain in the barrier property of the WPI film after adding silica coated TiO 2 and clay nanoparticles, respectively. Zolfi et al (2014) reported that WVP decreased by 57% with 5% clay addition while Sothornvit, et.…”
Section: Water Vapor Permeability Of the Filmsmentioning
confidence: 88%
See 2 more Smart Citations
“…Zhou et al (2009) used 4% TiO 2 and observed a 70% decrease in WVP while Zolfi et al (2014) and Li et al (2011) observed 14% and 9.4% decreases by adding 5% and 1% TiO 2 , respectively. Kadam et al (2013) and Sothornvit et al (2009) did not obtain any gain in the barrier property of the WPI film after adding silica coated TiO 2 and clay nanoparticles, respectively. Zolfi et al (2014) reported that WVP decreased by 57% with 5% clay addition while Sothornvit, et.…”
Section: Water Vapor Permeability Of the Filmsmentioning
confidence: 88%
“…With the addition of titania, Zhou et al (2009) andLi et al (2011) reached a maximum strength of 2.38 MPa (41% increment with respect to pure WPI film) and 10.2 MPa (67% increment), respectively. To achieve a homogeneous distribution of the nanoparticles, Kadam et al (2013) coated titania with silica, however, they observed only a slight increase in tensile strength from 1.03 to 1.18 MPa (15% increment). Zolfi et al (2014), Wakai and Almenar (2015) and Azevedo et al (2015) measured maximum tensile strengths of~11 MPa (57% increment with respect to pure WPI film), 2.3 MPa (16% increment) and 5.42 MPa (49% increment), respectively.…”
Section: Mechanical Properties Of the Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, among other biopolymers (Park et al, 2002;Petersson and Oksman, 2006;Almasi et al, 2010), whey protein-based nanocomposites have become a promising field of interest in recent years (Hedenqvist et al, 2006;Zhou et al, 2009;Sothornvit et al, 2010;Li et al, 2011;Kadam et al, 2013;Zolfi et al, 2014;Azevedo et al, 2015;Wakai and Almenar, 2015;Hassannia-Kolaee et al, 2016a,b;Oymaci and Altinkaya, 2016). Previous research on whey protein isolate (WPI) nanocomposites demonstrated that the barrier and mechanical properties of these materials improved with increasing nanofiller loadings (Sothornvit et al, 2010;Zolfi et al, 2014;Azevedo et al, 2015;Hassannia-Kolaee et al, 2016a;Oymaci and Altinkaya, 2016;Zink et al, 2016).…”
mentioning
confidence: 99%
“…Nanofillers (e.g., nanoclays) have been used to strengthen whey protein polymer matrices (Zhao et al, 2008). In an earlier report, we demonstrated that the mechanical properties of WPI and corn zein films could be improved by using porous silica (SiO 2 ) coated titania (TiO 2 ) nanoparticles as nanoenhancers (TiO 2 @@SiO 2 ) (Kadam et al, 2013).…”
mentioning
confidence: 99%